MODERN DIAGNOSTIC TOOLS FOR DETECTING HEPATIC FIBROSIS IN CHILDREN - A.N. Surkov (Union of pediatricians of Russia, 2009)
The present review highlights the new diagnostic tools for detecting hepatic fibrosis against the backdrop of different liver pathologies in children. They are characterized by a variety of the clinical forms, progressive course along with the fibroid changes in liver and possible result in the liver cirrhosis. The authors considered the modern methods of the needle liver biopsy and noninvasive visualization, as well as justified the necessity to look for the noninvasive markers of the fibroid liver by means of the antibody'mediated diagnostic methods. Such tests are based on identification of various molecular compounds, which are fibrogenesis activators and take part in the formation of the extracellular matrix components. They also described changes of such fibroid liver markers, as hyaluronic acid, collagen type IV, matrix metalloproteinases 2 and 9, tissular inhibitor of the matrix metalloproteinases'1, transforming growth factor-1, which may be recommended for the noninvasive monitoring of the hepatic fibrosis in children.Key words: hepatic fibrosis, antibody'mediated fibrosis markers, children.